Training Model to Improve Manager Performance in Non-Formal Education Units in Improving the Quality of Education Services - Saepudin, Asep; Akhyadi, Ade Sadikin; Saripah, Iip (Journal of Nonformal Education, 2020)
Non-formal education has proven to be able to improve the quality of education for the community, however, its implementation still faces many obstacles due to various limitations. Therefore, problem analysis and development efforts are needed. Based on the results of exploration, expectation data from managers of non-formal education units are needed regarding the need to foster the performance of managers in providing ideal and quality non-formal education services. This study focuses on three topics, as follows: (1) describing the conceptual model managers, (2) applying a training model, and (3) to analyze the effectiveness of the training model to improve the performance of the non-formal education unit managers. The research approach is qualitative with descriptive methods. The data collection techniques used in this research consisted of documentation studies, literature studies, interviews, and focus group discussions. The research subjects were 17 managers of non-formal education units in Bandung Raya, consisting of the managers of the Community Learning Center (CLC) and the Course and Training Institute (CTI). The research period has been carried out for six months. The results of this study are: First, improve the performance of non-formal education managers is prepared following the expectations of the manager. Second, improve the performance of the non-formal education unit managers is carried out through the planning, implementation, and evaluation stages. Third, improve the performance of non-formal education unit managers is considered effective, as evidenced by the increase in manager competence based on the results of the pretest and posttest.